Evaluation of the Activity of Choline Acetyltransferase From Different Synaptosomal Fractions at the Distinct Stages of Spatial Learning in the Morris Water Maze - Storozheva, Zinaida I.; Zakharova, Elena I.; Proshin, Andrey T. (Frontiers in Behavioral Neuroscience, 2021)
The numerous data evidenced that brain cholinergic circuits play crucial role in learning and memory, however, our knowledge about participation of neocortical and hippocampal cholinergic systems in spatial learning need to be refined. The aim of this study was to estimate the association of the activity of membrane-bound and soluble choline acetyltransferase (ChAT) in the synaptosomal sub-fractions of neocortex and hippocampus with performance of spatial navigation task in Morris water maze at different temporal stages of memory trace formation. To identify distinct stages of memory formation, rats were trained using 5 days x 4 trials protocol and the individual means of escape latency in each trial were processed by Principal Component Analysis. In the frame of used protocol, three relatively distinct stages (1st-2nd, 3rd and 4th -5th days) of memory formation were identified. Remotely stored memory trace tested in repeated and reversal learning 14 days after the end of initial training, was found to be associated at the individual level mainly with the performance on the 2nd stage (3rd day). Data on ChAT activity suggest the participation of cholinergic cortical projections mainly in the first stage of spatial learning (automatic sensory processing) and the involvement of hippocampal interneurons in the second (error-corrected learning) one. Cholinergic cortical interneurons participated mainly in the stage of asymptotic performance (4th-5th days). The study of other signaling pathways at identified stages of memory formation seems to be advisable.